2023
DOI: 10.3390/toxins15030182
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and Levels of Aflatoxin M1 in Artisanal and Manufactured Cheese in Pernambuco State, Brazil

Abstract: Cheese is one of the most susceptible dairy foods to accumulating aflatoxins due to their high affinity to caseins. The consumption of cheese contaminated with high levels of aflatoxin M1 (AFM1) can be highly harmful to humans. The present work, based on high-performance liquid chromatography (HPLC), highlights the frequency and levels of AFM1 in coalho and mozzarella cheese samples (n = 28) from the main cheese-processing plants in Araripe Sertão and Agreste in the state of Pernambuco, Brazil. Of the evaluate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
1
0
5

Year Published

2024
2024
2025
2025

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 41 publications
0
1
0
5
Order By: Relevance
“…In oats samples, Pinheiro et al (2021) found DON (44%), NIV (29%), 3-ADON (19%) and 15-ADON (8%). In beer, 80-100% of aflatoxins have been reported (Reboucas Rocha et al, 2023), and 21% of OTA was found in fermented coffee (Silva et al, 2023). In tilapia muscle, 19% of AFB 1 was found by Seraphin de Godoy et al (2022).…”
Section: Brazilmentioning
confidence: 97%
“…In oats samples, Pinheiro et al (2021) found DON (44%), NIV (29%), 3-ADON (19%) and 15-ADON (8%). In beer, 80-100% of aflatoxins have been reported (Reboucas Rocha et al, 2023), and 21% of OTA was found in fermented coffee (Silva et al, 2023). In tilapia muscle, 19% of AFB 1 was found by Seraphin de Godoy et al (2022).…”
Section: Brazilmentioning
confidence: 97%
“…V mlieku sa AFM1 silne viaže na kazeíny a preto, vyššie hladiny AFM1 možno očakávať v mliečnych výrobkoch s vysokým obsahom bielkovín, ako je syr. Okrem toho, tradičné tepelné spracovanie mlieka, ako je pasterizácia alebo sterilizácia, neničia jeho molekuly (Silva et al, 2023).…”
Section: úVodunclassified
“…Mesmo quando as condições ambientais são favoráveis, a ocorrência dessas substâncias é inevitável (Qu et al, 2022). Gêneros fúngicos proeminentes como Aspergillus, Fusarium, Penicillium e Alternaria, destacam-se como produtores significantes de micotoxinas, tendo a capacidade de contaminar extensas áreas agrícolas e, por consequência, os produtos finais destinados ao consumo humano (El-Sayed et al, 2022; I. M. de M. Silva et al, 2023).…”
Section: Micotoxinasunclassified
“…Isso pode ocorrer devido à produção aumentada de substâncias tóxicas por esses fungos, sob condições favoráveis (Ismail et al, 2018). As aflatoxinas (AFLA) demonstram estabilidade térmica, resistindo a temperaturas superiores a 100 °C, o que impede sua degradação durante o processamento de alimentos (Gonçalves et al, 2017;Gonçalves, Muaz, et al, 2020), como leite e derivados (I. M. de M. Silva et al, 2023). Isso ocorre uma vez que os métodos tradicionais de tratamento térmico, incluindo a pasteurização, têm se mostrado insuficientemente eficazes (Dhakal et al, 2023;Guan et al, 2021;Ismail et al, 2018).…”
Section: Aflatoxinasunclassified
See 1 more Smart Citation